A Modified Electrosurgery Unit Based on High Frequency Design with Monopolar and Bipolar Method - Edo Rafsanzani; Tri Bowo Indrato; Andjar Pudji; Shengjie Yan; Sergey A. Bogavev (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2021)
Electrosurgery Unit is some machine to human body surgery. Electrosurgery Unit is uses a high frequency to human body tissue surgery, that causes blood who came out can be dicrease during surgery. When using a conventional scalpel is something that is highly avoided because it will cause contraindications to lack of blood which will be very dangerous for the patient. The purpose of this study is to design a tool that is used to replace a conventional scalpel with a tool that utilizes high frequency (400 KHz) generated by the oscillator circuit. In this study. The researches used Monopolar method and used two modes Cutting and Coagulation in order to eliminate faradic effects on body tissues causes high frequency, there is the high frequency will be adjusted to the duty cycle which aims to obtain various types of surgery required by doctor which is cutting 100% on and coagulation 6% on 94% off where is set it with arduino program. In this study, the researchers took advantage of the type of heat effect produced by high frequencies which were concentrated at one point so that it could be used to carry out the process of surgery on body tissues so as to minimize the occurrence of large blood loss. The result of this study is will be centered at one point on an object there is show up the depth difference of the cutting mode and the wide large difference of the coagulation mode. The module design resulted the power lowest at 300Ohm ESU Analyzer setting is 30Watt and the highest at 300Ohm setting too is 68Watt. The module design resulted the power lowest at 300Ohm ESU Analyzer setting is 30Watt and the highest at 300Ohm setting too is 68Watt at mode Cutting and the highest and lowest Coagulation mode using impedance setting the same there is 300 Ohm is constant 3Watt power result’s. The weaknesses at this research is the power still lower then the Electrosurgery Unit where is in the hospital. It can be fix for the next research using increase the final amplifier and maybe increase the frequency where is gonna make the voltage of the final amplifier be much better then this research